PENGARUH SUPERVISI DAN SARANA PRASARANA DENGAN KINERJA PERAWAT - Andoko Andoko; Intan Putri (Universitas Malahayati Lampung, 2020)
ABSTRACT Background: The quality of nursing care given by a nurse can be measured by making an evaluation system known as performance assessment. There are three factors influencing performance, they are individual factor, organizational factor and psychological factor. The aspects of organizational factor are supervision and infrastructure.Purpose: This study scrutinized the effect of supervision and infrastructure towards nurse performance at care wards of A Dadi Tjokrodipo Hospital of Bandar Lampung in 2019.Methods: This is a quantitative study with cross sectional approach. The population of this study is the whole nurse in charge at A Dadi Tjokrodipo Hospital of Bandar Lampung amounting to 46 people. The respondents are 46 people. The data collection technique was conducted by using questionnaire. The statistical test was done with chi square.Results: Frequency distribution of respondents stated good supervision as many as 24 respondents (52.2%), respondents stated good infrastructure as many as 26 respondents (56.5%), respondents stated good performance as many as 27 respondents (58.7%). There is an influence of supervision with nurse performance (p value 0.041. OR 4.3). There is the influence of facilities and nurse performance (p value 0.002. OR 9.8) in the Inpatient Room of RSUD A Dadi Tjokrodipo Bandar Lampung.Conclusion: There is an influence of supervision and facilities with nurse performance. Suggestions on research to nursing care institutions in hospitals through the field of nursing in collaboration with the hospital management to develop their careers by continuing their education and enhancing nursing experience and motivating Nurse's performance is always good. Keywords: infrastructure, supervision, nurse performance Pendahuluan: Kualitas pelayanan keperawatan yang diberikan oleh perawat dapat diketahui melalui suatu evaluasi yaitu penilaian kinerja. Terdapat tiga faktor yang mempengaruhi kinerja, yaitu faktor individu, faktor organisasi dan faktor psikologi. Salah satunya faktor organisasi adalah supervisi dan sarana prasarana.Tujuan: diketahui pengaruh antara sarana prasarana dan supervisi dengan kinerja perawat di Ruang Rawat Inap RSUD A Dadi Tjokrodipo Bandar Lampung Tahun 2019.Metode: Jenis penelitian kuantitatif, menggunakan pendekatan cross sectional. Populasi pada penelitian ini adalah seluruh perawat pelaksana di RSUD A Dadi Tjokrodipo Bandar Lampung sejumlah 46 orang. Sampel 46 responden. Tehnik pengumpulan data dilakukan dengan menggunakan kuesioner. Uji statistik yang digunakan adalah uji Chi Square.Hasil: menunjukkan Distribusi frekuensi responden menyatakan supervisi baik yaitu sebanyak 24 responden (52,2%), sarana prasarana baik yaitu sebanyak 26 responden (56,5%), kinerja baik yaitu sebanyak 27 responden (58,7%). Ada pengaruh supervisi dengan kinerja perawat (p value 0,041. OR 4,3). Ada pengaruh sarana prasarana dengan kinerja perawat (p value 0,002. OR 9,8). Kesimpulan: ada pengaruh supervisi dan sarana prasarana dengan kinerja perawat. Saran pada penelitian kepada Institusi pelayanan keperawatan agar terus mengembangkan kariernya dengan melanjutkan pendidikan dan meningkatkan pengalaman tentang keperawatan serta memotivasi agar kinerja perawat tetap selalu baik. Kata Kunci : Sarana Prasarana, Supervisi, Kinerja Perawat